1999
DOI: 10.1111/j.1469-8749.1999.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Fingertip forces during object manipulation in children with hemiplegic cerebral palsy. I: Anticipatory scaling

Abstract: Previous studies of grasping and object manipulation in children with cerebral palsy (CP) have suggested a dichotomy in the ability to use anticipatory control (planning) of the fingertip force output, depending on the type of sensory information (tactile or proprioceptive) on which it is based. The present study further explores this issue by testing the ability of 15 children with hemiplegic CP aged between 8 and 14 years to scale the fingertip force output in advance during the lifting of small objects whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 31 publications
(28 reference statements)
3
60
0
1
Order By: Relevance
“…Children were instructed to grasp the object between the thumb and the index finger ("precision grip") and lift it so that it was adjacent to a marker 5 cm high. They often used their middle finger against the index finger nail for additional support ("three-digit pinch") and/or lifted the instrument between the thumb and lateral portion of their index finger ("lateral pinch") when using their "involved" hand, which we have shown does not affect the use of anticipatory force scaling (7).…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…Children were instructed to grasp the object between the thumb and the index finger ("precision grip") and lift it so that it was adjacent to a marker 5 cm high. They often used their middle finger against the index finger nail for additional support ("three-digit pinch") and/or lifted the instrument between the thumb and lateral portion of their index finger ("lateral pinch") when using their "involved" hand, which we have shown does not affect the use of anticipatory force scaling (7).…”
Section: Methodsmentioning
confidence: 76%
“…In agreement with earlier studies, children with hemiplegic CP use a default force scaling in their involved hand, regardless of object weight (6 -8), suggesting impaired anticipatory force control. However, with enough practice, children with CP can learn to differentiate the force scaling according to object weight (7,8), indicating that the lack of anticipatory scaling in other studies was not due to an inability to graduate the force output (i.e. an impairment in motor execution).…”
mentioning
confidence: 86%
“…1,24,26 The criteria included (1) the ability to extend the wrist Ն20°and the metacarpophalangeal joint 10°from full flexion, 32 (2) a 50% difference between the involved and noninvolved hand on the Jebsen-Taylor Test of Hand Function, 33 (3) a score within 1 SD from the mean on the Kaufman Brief Intelligence Test, 34 and (4) willingness to agree to intervention and testing procedures and travel to the university for participation. Children were excluded who had (1) any health problems that are not associated with CP, (2) seizures, (3) visual problems that would prevent them from carrying out the intervention or testing tasks, (4) severe muscle tone (Modified Ashworth score of Ͼ3), (5) orthopedic surgery on their more affected upper extremity, (6) experienced a dorsal rhizotomy, (7) received botulinum toxin therapy in the upper-extremity musculature during the last 6 months or who wish to receive it within the period of study, (8) received intrathecal baclofen, and (9) balance problems while wearing the restraint.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
“…1 This disuse, in turn, may lead to additional impairments secondary to neural damage associated with CP. Interestingly, we have found that, in the laboratory environment, repetitive practice of a motor task with the involved hand can result in improved performance 2,3 in a relatively short time period. This observation suggests that the involved upper extremity is amenable to treatment and that intensive practice may be beneficial to improve function.…”
mentioning
confidence: 90%
“…Unfortunately, evidence-based treatments of impaired hand function are largely lacking. 4 Children with hemiplegia may benefit from intensive unimanual practice, 5 intensive contemporary occupational therapy 6 or goal-directed training combined with botulinum toxin. 7 One recent treatment approach providing intensive unimanual practice, constraint-induced movement therapy (CIMT), has shown promise for the improvement of unimanual hand function.…”
mentioning
confidence: 99%